Formulation of a Model for Employee Empowerment and Job Embeddedness with the Mediating Role of Social Capital in National Sports Federations - Khani Kalkhoran , Taher; Nasiri, Mohammad; Imanzadeh, Masoud; Moharamzade , Mehrdad (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: The objective of this study is to develop a model for employee empowerment and job embeddedness in sports federations, emphasizing the mediating role of social capital. Methodology: This research is applied in nature and employs a descriptive-correlational methodology. Data were collected through standardized questionnaires, including Sprietzer’s Job Empowerment Questionnaire (1995), Putnam’s Social Capital Questionnaire (2005), and Edwards and Kilpatrick’s Job Embeddedness Questionnaire (1984), all using a 5-point Likert scale. The sample consisted of 269 randomly selected employees from the total population of 901 employees in national sports federations. Data analysis was conducted using Structural Equation Modeling (SEM) through SPSS and LISREL software to test the hypothesized relationships between empowerment, job embeddedness, and social capital. Findings: The results indicate that the relationship between employee empowerment and job embeddedness is significantly mediated by social capital. The path coefficient for the impact of empowerment on job embeddedness was 0.59, and the mediating role of social capital had a path coefficient of 0.67. The model fit indices, including RMSEA (0.080), GFI (0.91), AGFI (0.97), and NFI (0.91), demonstrate an acceptable fit for the proposed model. The analysis also showed that increasing social capital strengthens the relationship between empowerment and job embeddedness, while decreasing social capital weakens this relationship. Conclusion: This study concludes that employee empowerment and job embeddedness are closely linked through the mediating influence of social capital. Enhancing social capital in sports federations can significantly improve employee retention and productivity.